2008
DOI: 10.1103/physrevd.78.083524
|View full text |Cite
|
Sign up to set email alerts
|

Determining cosmological parameters with the latest observational data

Abstract: In this paper, we combine the latest observational data, including the WMAP five-year data (WMAP5), BOOMERanG, CBI, VSA, ACBAR, as well as the Baryon Acoustic Oscillations (BAO) and Type Ia Supernoave (SN) "Union" compilation (307 sample), and use the Markov Chain Monte Carlo method to determine the cosmological parameters, such as the equation-of-state (EoS) of dark energy, the curvature of universe, the total neutrino mass and the parameters associated with the power spectrum of primordial fluctuations. Our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
77
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 88 publications
(79 reference statements)
13
77
0
1
Order By: Relevance
“…[67], the authors used the first year WMAP, SDSS and 2dFGRS data to constrain the DE models, and they found that the data evidently favor a strongly time-dependent w DE at present, which is consistent with other results in the literature [68,69,70,71,72,73,74,75,76,77]. As observed in Fig.5, using the latest 5-year WMAP data, combined with SNIa and BAO data, the constraints on the DE parameters of Model B are: w 0 = −1.06 ± 0.14 and w 1 = 0.36 ± 0.62 [34,78,79]. Thus, one deduces that current observational data mildly favor w DE crossing the phantom divide during the evolution of universe.…”
Section: Observational Evidence For Quintom De Scenariosupporting
confidence: 79%
“…[67], the authors used the first year WMAP, SDSS and 2dFGRS data to constrain the DE models, and they found that the data evidently favor a strongly time-dependent w DE at present, which is consistent with other results in the literature [68,69,70,71,72,73,74,75,76,77]. As observed in Fig.5, using the latest 5-year WMAP data, combined with SNIa and BAO data, the constraints on the DE parameters of Model B are: w 0 = −1.06 ± 0.14 and w 1 = 0.36 ± 0.62 [34,78,79]. Thus, one deduces that current observational data mildly favor w DE crossing the phantom divide during the evolution of universe.…”
Section: Observational Evidence For Quintom De Scenariosupporting
confidence: 79%
“…Currently, various observational data favor the simplest concordance cosmological model, which has six free parameters and the pure adiabatic initial condition [1,[3][4][5][6]. Although the concordance model fits the data quite well, it is always worthy to consider alternative candidates.…”
Section: Introductionmentioning
confidence: 99%
“…The above results were obtained from a combination of CMB measurements from the first-year Wilkinson Microwave Anisotropy Probe (WMAP) observations (Bennett et al 2003), the galaxy power spectrum based on the Sloan Digital Sky Survey (SDSS) Data Release 2 (Tegmark et al 2004), the SNe Ia data from Riess et al (2004), and the H 0 prior from the Hubble Space Telescope (HST) Key Project with H 0 =72±8 km s −1 Mpc −1 (Freedman et al 2001). The two models studied in Hannestad (2005) were also constrained in Wang et al (2012) with updated cosmological data, where the (Xia et al 2007(Xia et al , 2008Li & Xia 2012), and revealed the degeneracy between å n m and the EoS ω parameters. In Smith et al (2012), it was found that with non-vanishing curvature density parameter W ¹ 0 k the 95% upper limit on å n m was more than double with respect to the case of a flat universe.…”
Section: Introductionmentioning
confidence: 99%